National Histories of the Book in a Transnational Age - Lyons, Martyn (Mémoires du livre / Studies in Book Culture, 2016)
In the 1990s and 2000s, national histories of the book achieved a double milestone: firstly, they marked the coming to maturity of the subdiscipline of the history of the book itself, especially in English-speaking countries; at the same time they established landmarks in the cultural history of their own countries. My presentation will discuss the fate and the impact of national book histories from the point of view of the History of the Book in Australia, which I coedited and to which I contributed several chapters. Two historiographical events have challenged the agenda of national book histories. The ‘transnational turn’ has thrown into question the fundamental framework which governed their conception and production. To a lesser extent, the growth of the digital humanities also makes a radical departure from the ‘traditional’ research methods of the 1990s. My presentation will assess the legacy of the History of the Book in Australia so far, and ask whether national book history has any role to play in the age of transnational approaches. I will suggest in answer to my own question that there remains a place at the table for all three levels—transnational, national and also micro-histories of the book.